Modern Conception of the Control over the Abundance of Carriers and Vectors of Plague in the Territory of the Russian Federation - A. N. Matrosov; A. A. Kuznetsov; T. V. Knyazeva; D. B. Verzhutsky; A. Ya. Nikitin; L. S. Nemchenko; M. P. Grigor'ev; B. I. Levchenko; O. A. Bobenko; A. Yu. Gazieva; V. B. Korotkov (Проблемы особо опасных инфекций, 2012)
Disinfestation and deratization remain the main ways of non-specific disease prophylaxis in natural plague foci. Modern strategies, tactics, methods and means of control over carriers and vectors of plague and associated infectious diseases are selected with due consideration to epidemiological potential of territories, epizootic activity of a foci, peculiarities of population ecology of animals that are of a medical significance, preservation of biodiversity in natural ecosystems, and the requirements for human and natural environments protection from pollutants.